Binary micellar solutions of poly (Ethylene Oxide)-poly(Styrene Oxide) copolymers with pluronic P123 : drug solubilisation and cytotoxicity studies - Oliveira, Samira A. (2015)
The non-commercial copolymers E45S8, E45S17 and their mixtures with Pluronic® P123 (E21P67E21) were studied as carriers of the model drug griseofulvin. Critical micelle concentration (cmc) (dye solubilisation method), drug solubilisation capacity (Scp and Sh) determined by ultraviolet-visible (UV-Vis) spectroscopy and 1H nuclear magnetic resonance (1H NMR) and cytotoxicity (LDH activity in human neutrophils) were studied. E45S17 1.0 wt.% dispersions presented colloidal aggregates limiting its Scp in comparison to E45S8, but in 0.1 wt.% solutions this phenomenon seemed to be absent and E45S17 presented a higher Scp. The mixtures that showed the best Scp results contained 50% of P123 and presented low cmc. An evaluation of literature data suggested a minimum Em content of 62% in EmSn copolymers below which the increase of Sn length does not lead to an increase of Sh. The results suggested no toxicity of the copolymers on human neutrophils, supporting the use of P123 and poly(styrene oxide) containing copolymers as drug carriers.